MERAIH NILAI TAMBAH TEKNOLOGI INFORMASI BAGI PERUSAHAAN - Sylvia Sylvia (AkMen JURNAL ILMIAH, 2009)
A lot of way of approach to instruct will be brought by where decision of invesment of information technology taken by company head. Company might possibly chosen to use the information system strategically, or company can lick lips by using TI to support the efficient routine operation. If company emphasize the use of information technology for the strategy of business, hence application management of TI as distinguishing factor [of] prima facie kompetitif. Management party will compile various strategy using TI to develop various product, service, ability to give the big excellence company in market of company place compete the